1980
DOI: 10.1111/j.1530-0277.1980.tb04809.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Ethanol on Liver Blood Circulation in the Anesthetized Dog

Abstract: A single, intraportal injection of ethanol (0.01 g/kg body weight) in the pentobarbital anesthetized dog elicited an immediate rise in the hepatic resistance to both portal and hepatic blood flows. Similar effects were produced by norepinephrine and these, as well as those of ethanol, were significantly reduced by yohimbine. Increased levels of noradrenaline were found in hepatic venous effluent during the vasoconstriction period induced by ethanol. We postulate that noradrenaline liberated from sympathetic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Another possible mechanism for an increased hepatic vas cular resistance is that ethanol acts pharmacologically by releasing nor adrenaline from hepatic nerve endings. This hypothesis is supported by a recent study by Bravo et al [3] in dogs. A single intraportal injection of ethanol resulted in a resistance to portal flow and a reduction in blood content of the liver.…”
Section: Discussionsupporting
confidence: 81%
“…Another possible mechanism for an increased hepatic vas cular resistance is that ethanol acts pharmacologically by releasing nor adrenaline from hepatic nerve endings. This hypothesis is supported by a recent study by Bravo et al [3] in dogs. A single intraportal injection of ethanol resulted in a resistance to portal flow and a reduction in blood content of the liver.…”
Section: Discussionsupporting
confidence: 81%
“…However, the precise mechanism by which ethanol causes nitric oxide release and the site(s) on which nitric oxide acts in the presence of ethanol remain to be elucidated. To date, reports conflict over the effect of ethanol on hepatic hemodynamics (29)(30)(31)(32)(33). Previous studies by several investigators indicated increases in portal pressure (29,30), whereas others indicated no effect (31)(32)(33).…”
Section: Discussionmentioning
confidence: 84%
“…Simi larly, an increased hepatic vascular resistance has been observed in dogs following an intra portal injection of alcohol [2]. Therefore, it seems likely that the reduction in portal ve nous flow and liver blood in this study with higher rates of alcohol infusion was, at least in part, due to an increased intrahepalic resis tance to portal flow.…”
Section: Discussionmentioning
confidence: 76%
“…The mechanism where by alcohol increases intrahepatic resistance is not clear. Bravo et al [2] observed that in the dog changes in hepatic haemodynamics fol lowing intraportal injections of either alcohol or noradrenaline were similar and that the hepatic response to both substances was in hibited by yohimbine. Moreover, intraportal administration of alcohol increased the con centration of noradrenaline in hepatic ve nous blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation